THE RELATIONSHIP OF PARENTS' THERAPEUTIC COMMUNICATION WITH SOCIAL DEVELOPMENT OF PRESCHOOL AGE CHILDREN 3-6 YEARS OLD IN PULOKALAPA VILLAGE IN 2022.: HUBUNGAN KOMUNIKASI TERAPEUTIK ORANG TUA DENGAN PERKEMBANGAN SOSIAL ANAK USIA PRASEKOLAH 3-6 TAHUN DI DESA PULOKALAPA TAHUN 2022 - Kusmawati, Sisfa; Agustina, Lisna; Gea, Nurti Yunika Kristina (Borneo Nursing Journal (BNJ), 2023)
Communication is the delivery of messages to other people to inform or change behavior, opinions, or attitudes, either directly or indirectly through the media. Parental communication, namely communication with children, can be called interpersonal communication, communication as a process of exchanging meaning between people who communicate with each other. In this study, parents and children indirectly carry out interpersonal communication considering the importance of communicating with children to know what the child's development feels like. Development is a process that never stops (never ending process), meaning that humans are continuously developing, influenced by experience or learning.